2012 IEEE Energytech 2012
DOI: 10.1109/energytech.2012.6304679
|View full text |Cite
|
Sign up to set email alerts
|

A review of intelligent control techniques in HVAC systems

Abstract: Two main objectives in the control of Heating, Ventilating and Air Conditioning (HV AC) systems are increasing thermal comfort and reducing energy consumption. Achieving these purposes requires a suitable control system design. In this paper, a thorough review of intelligent control techniques used in HV AC systems to date is completed. Such an overview provides an insight into artificial intelligence methods for the control of HV AC systems and can offer scholars and HV AC learners comprehensive information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…Due to lots of disturbances, time delays, contingencies and vagueness about thermal comfort, make finding a proper mathematical model for the system much more difficult [69]. According to the structure of the intelligent control methods, a model of the system is not required for designing the controller and it only depends on the human's thermal comfort feeling.…”
Section: Soft Control Category or Intelligent Control Categorymentioning
confidence: 99%
“…Due to lots of disturbances, time delays, contingencies and vagueness about thermal comfort, make finding a proper mathematical model for the system much more difficult [69]. According to the structure of the intelligent control methods, a model of the system is not required for designing the controller and it only depends on the human's thermal comfort feeling.…”
Section: Soft Control Category or Intelligent Control Categorymentioning
confidence: 99%
“…Therefore, modeling BEMS performance using traditional methods is difficult [18]- [20]. However, it has been shown that fuzzy modeling is suited to model the non-linearity and interrelationships between different data sources existing in BEMSs [15], [17]. Similarly, human occupant comfort is also highly subjective, and also relies on a large number of factors [14], [20].…”
Section: Linguistic Rule Based Behavior Extractionmentioning
confidence: 99%
“…Therefore, building HVAC control is a multi criteria optimization problem that tries to maintain human occupant comfort while increasing the energy efficiency [16], [17]. In order to achieve these goals, modern buildings use advanced control systems known as Building Energy Management Systems (BEMSs).…”
Section: Introduction (Heading 1)mentioning
confidence: 99%
“…These classical methods have been investigated extensively in HVAC lower-loop controls [4][5][6], such as room temperature control [7][8][9] and supply air temperature control [10][11][12]. Despite their popularity, these classical methods do not perform optimally.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The REINFORCE [38] policy gradient provides an unbiased estimate of the gradient of the policy with respect to the objective function J(θ) given in Equation (6).…”
Section: Policy Gradientmentioning
confidence: 99%